Comparing the characteristics and outcomes of parent‐ and teacher‐reported oppositional defiant disorder: findings from a national sample. (12th December 2017) - McNeilis, James; Maughan, Barbara; Goodman, Robert; Rowe, Richard
Abstract : Background: Parents and teachers often disagree on the presence of Oppositional Defiant Disorder (ODD) in children. It has been argued that ODD should be treated as an informant‐specific disorder. This study compared the characteristics of children identified with ODD by parent‐ and teacher report. Methods: We used the 1999 British Child and Adolescent Mental Health Survey, including more than 10, 000 observations aged 5–15 years, to investigate symptom profiles, risk factors, comorbidities and three‐year outcomes of parent‐ and teacher‐reported ODD. Results: Parents and teachers poorly agreed on ODD diagnosis. Parent‐reported ODD was more strongly associated with a concurrent anxiety disorder at time1 and a successive diagnosis of ODD at time2 . Beyond these differences, parent‐ and teacher‐ reported ODD showed similar symptom profiles, risk factors, comorbidities, and outcomes. Conclusions: Children identified by parent report and teacher report share more similarities than differences in the characteristics of their disorder. This does not support the formation of informant‐specific ODD disorders.